ONECUT2 reprograms neuroendocrine fate and is an actionable therapeutic target in small cell lung cancer - Mirian Gutiérrez; Irene Zamora; Raquel Iriarte; María José Pajares; Qian Yang; Chen Qian; Nerea Otegui; Joaquín Fernández-Irigoyen; Enrique Santamaría; Nicolas Alcala; Alexandra Sexton-Oates; Lynnette Fernández-Cuesta; et al. (Molecular Medicine)
Abstract Small cell lung cancer (SCLC) is a highly aggressive malignancy with extremely poor prognosis. SCLC cells exhibit high plasticity and can progress from neuroendocrine (NE) to non-NE phenotypes. This dynamic evolution promotes treatment resistance and relapses, representing a challenge for targeted therapies in this elusive disease. Here we identify the transcription factor ONECUT2 (OC2) as a driver of plasticity in SCLC, leading to non-NE transcriptional states. OC2 is highly expressed in SCLC tumors compared to normal lung tissue and its expression is associated with heightened clinical stage and lymph node metastasis. We show that OC2 is a repressor of ASCL1, the NE master regulator transcription factor. In addition, OC2 upregulates non-NE programs through activation of c-MYC and Notch signaling. We also demonstrate that OC2 is required for growth and survival of SCLC cells and that it can be targeted with a small molecule inhibitor that acts synergistically with the standard combination of cisplatin and etoposide, providing a novel therapeutic strategy for OC2 active SCLC tumors.